THE COOL GIANT STARS IN SOLAR VICINITY - Komarov, N. S.; Korotina, L. V.; Shevchuk, T. V. (Одеські астрономічні публікації, 2017)
The data of absolute spectrophotometry were used for determination of the characteristics for 700 standards’ stars in spectral region from G0 to M4. The 170 stars were selected for calibration of new photometric indicies obtained by using a multicolour photometric catalogue in Geneva observatory and Gildenkern’s systems. Effective temperatures, gravities and rnetallicities have been determinated for 1000 stars of Geneva observatory and for 600 stars of Gildenkern’s systems in the region of spectral types from G0 to K5.